2011
DOI: 10.1007/s00428-011-1072-3
|View full text |Cite
|
Sign up to set email alerts
|

Histologic grading of urothelial papillary neoplasms: impact of combined grading (two-numbered grading system) on reproducibility

Abstract: The clinical management of tumor patients is often strongly influenced by the tumor grade. The presence of heterogeneity is well recognized in a variety of tumors. Overall grade is based on highest grade area identified within a tumor. Urothelial carcinoma often contains different histological grades within the same tumor. This study investigates the impact of a combined grading system on the reproducibility of papillary urothelial neoplasms. A set prepared for an earlier study consisting of ten cases of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Moreover, and probably more importantly, the actual cut-off points of histological classification are subject to interobserver variation. 25,26 In fact, all the low-grade NIPUC cases in our study were diagnosed originally as PUNLMP or even inverted papilloma. Although our study found no TERT promoter mutation in any case of inverted papilloma, Cheng et al reported TERT promoter mutations in 15% (four of 26) cases of inverted papillomas.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, and probably more importantly, the actual cut-off points of histological classification are subject to interobserver variation. 25,26 In fact, all the low-grade NIPUC cases in our study were diagnosed originally as PUNLMP or even inverted papilloma. Although our study found no TERT promoter mutation in any case of inverted papilloma, Cheng et al reported TERT promoter mutations in 15% (four of 26) cases of inverted papillomas.…”
Section: Discussionmentioning
confidence: 79%
“…In our study, the prognostic value of TERT promoter mutations fell to an equivocal level if PUNLMP and low‐grade NIPUC cases were mixed ( P = 0.052). Moreover, and probably more importantly, the actual cut‐off points of histological classification are subject to interobserver variation . In fact, all the low‐grade NIPUC cases in our study were diagnosed originally as PUNLMP or even inverted papilloma.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, as the tumour grade of all patients with NMIBC was always assigned to a single expert uro-pathologist, the interobserver discrepancy for grading attribution could not be addressed. It should be recognised that, although a single-pathologist report can be seen as an advantage with respect to the continuity of the process over the years and reflecting many clinical routine contexts, it may also be considered the major criticism of the present results [21][22][23][24]. The absence in the multivariable analysis of histological microstaging and lymphovascular invasion (available for ∼50 and 30% of cases, respectively) might be considered as an additional limiting factor for results interpretation [25][26][27].…”
Section: Discussionmentioning
confidence: 88%
“…In a recent study published by May, the agreement on grade among four pathologists was 38-73% when using the 1973 WHO classification and 72-83% when using the 2004 WHO/ ISUP classification [36]. Analogous values in previously published studies were in the ranges of 17-80% and 33-95%, respectively [30,[37][38][39][40][41][42][43][44][45]. These data are presented in Table V.…”
Section: Gradingmentioning
confidence: 54%